The effect and design of time delay in feedback control for a nonlinear isolation system. (15th March 2017) - Sun, Xiuting; Xu, Jian; Fu, Jiangsong
Abstract: The optimum value of time delay of active control used in a nonlinear isolation system for different types of external excitation is studied in this paper. Based on the mathematical model of the nonlinear isolator with time-delayed active control, the stability, response and displacement transmissibility of the system are analyzed to obtain the standards for appropriate values of time delay and control strengths. The effects of nonlinearity and time delay on the stability and vibration response are discussed in details. For impact excitation and random excitation, the optimal value of time delay is obtained based on the vibration dissipation time via eigenvalues analysis, while for harmonic excitation, the optimal values are determined based on multiple vibration properties including natural frequency, amplitude death region and effective isolation region by the Averaging Method. This paper establishes the relationship between the parameters and vibration properties of a nonlinear isolation system which provides the guidance for optimizing time-delayed active control for different types of excitation in engineering practices. Highlights: Utilizing time delay as adjustable parameter in active control. Building the relationship between vibration properties of the isolator and parameters theoretically. Obtaining the optimal values of time delay for different excitations and isolation requirements. Multi-steady states band induced by strong nonlinearity and effective isolation frequency band of nonlinear system are considered as two standards in analysis.